Analysis of the mechanical behavior of the matrix of a cementitious composite with addition of disperse carbon nanotubes (CNTs) using ultrasound (Research, Society and Development, 2022)
Carbon nanotubes (CNTs) have a carbon structure with a cylindrical shape with a variable diameter between 0.4 and 10 mm. As it is a very thin product, it is a material with the potential to be inserted in cementitious composites to reduce the number of voids in the mixture. This work aims to add carbon nanotubes in a cement matrix with Portland cement, evaluating the dispersion in the cured cement matrix and the impacts on its mechanical strength. Thus, samples were prepared containing different percentages of carbon nanotubes dispersed through the ultrasonic dispersion method and tests were performed for analysis. The analysis was carried out through tests of compressive strength, flexural and compressive strength, water absorption, void ratio, specific mass, water absorption by capillarity, and analysis by Scanning Electron Microscope, added to the EDS technique, at ages 7, 28 and 56 days. The results obtained in this study point to improvements with the use of nanotubes, favoring the mechanical behavior of the matrices. The process of mixing the nanotubes in the concrete additive proved to be favorable for its dispersion.